Knut H. Røed; Studies on the genetic structure of populations of reindeer and caribou (Rangifer tarandus L.) - Sven Skjenneberg (ed.) (Rangifer, 1987)
Knut H. Røed successfully defended his thesis for the Dr.agric degree at the Norwegian University of Agriculture on 9. October, 1986.